Representation of Teachers' Lives through Memes in Indonesia and United States: A Multimodal Analysis - Pandia, Betharia Sembiring (JAMI: Jurnal Ahli Muda Indonesia, 2025)
This study employed a descriptive qualitative design and adopts a social semiotics approach to investigate how memes portray the lives of teachers in Indonesia and the United States. Memes, as a form of digital narrative, offer unique insights into culturally specific experiences and societal perceptions of educators. This study analyzed a selection of widely circulated memes to understand how semiotic resources - such as imagery, text, and symbols are mobilized to construct meanings about teachers’ roles and challenges. Through this lens, memes are not only seen as entertainment but also as sites of social commentary that influence public discourse on education. By focusing on humor and social critique, memes revealed deeper societal attitude toward the teaching profession, including issues related to teacher identity, economic challenges, and the status of educators in different cultural contexts. By using descriptive qualitative method, it was found that in Indonesia, for instance, memes frequently highlight the struggles faced by guru honor (honorary teachers), drawing attention to the impact of financial instability on perceptions of educational quality. In addition, the challenges that teachers have to face in Indonesia was clearly depicted through the images of criminalization in educational sector. Meanwhile, in U.S memes depicted teachers as a profession with a heavy workload. To represent this meaning, the memes in U.S mostly used animals as their modes such as cats and squirrels to represent their fast-paced job. The findings suggest that memes play a significant role in shaping and reflecting public perceptions, contributing to broader conversations about the value of education and the evolving identity of teachers in a digital era. Key Words Memes, Multimodality, Social Semiotics, Teachers